2004
DOI: 10.1108/14626000410537100
|View full text |Cite
|
Sign up to set email alerts
|

Small business performance: a tourism sector focus

Abstract: Discussion and analysis of small businesses tends to work on generalised, popularised understanding and knowledge of what their motivations are and how they behave in a business environment. The need to explore below these generalisations into the submerged variables and relationships is argued in this paper if academics and policy makers seriously want to interpret and induct theory and practice from the key actors within their natural habitat. Thus, this paper provides a conceptual framework relative to smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
91
2
7

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(111 citation statements)
references
References 11 publications
10
91
2
7
Order By: Relevance
“…It is also often unlikely for tourism operators and SMEs in particular to initiate networks and collaboration possibilities on their own (Kelliher & Reinl, 2011;Morrison & Teixeria, 2004) and tourism operators are not always willing to collaborate with other sectors (Mei, Arcodia, & Ruhanen, 2013).…”
Section: Network and Collaboration From A Project Perspectivementioning
confidence: 99%
“…It is also often unlikely for tourism operators and SMEs in particular to initiate networks and collaboration possibilities on their own (Kelliher & Reinl, 2011;Morrison & Teixeria, 2004) and tourism operators are not always willing to collaborate with other sectors (Mei, Arcodia, & Ruhanen, 2013).…”
Section: Network and Collaboration From A Project Perspectivementioning
confidence: 99%
“…Some entrepreneurs choose not to expand the firms because that would be in contrast with their desire to retain control of decision making (Glancey, 1998). For instance, in Morrison and Teixeira's (2004) study the owners perceived that growth will result in loosing distinctive attributes associated with smallness, while from managerial perception it is deemed undesirable because of financial and human resource poverty.…”
Section: Organisational Contextmentioning
confidence: 99%
“…Analysing models of entrepreneurship, Shaw and Williams (1998) A few studies also revealed the mutual existence of lifestyle and business goals. Exploring small accommodation providers in Scotland, Morrison and Teixeira (2004) found that business entry motivations reflected a mix of personal and business circumstances, but are dominated by those associated with family. This was also confirmed by Hall and Rusher (2004) analysing Bed and Breakfast operators in New Zealand, and Shaw and Williams (2004) in a study of 'surf-entrepreneurs' in Cornwall, England.…”
Section: Organisational Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…The last example of a group of firm performance measures could include four indicators used by Morrison and Teixera (2004). In their research concerned with small business performance focused particularly on tourism sector, firm performance was measured by bedroom occupancy rate, annual revenue, break-even point, and guest satisfaction.…”
Section: Objective Subjectivementioning
confidence: 99%